2010
DOI: 10.1371/journal.ppat.1001135
|View full text |Cite
|
Sign up to set email alerts
|

Release of Intracellular Calcium Stores Facilitates Coxsackievirus Entry into Polarized Endothelial Cells

Abstract: Group B coxsackieviruses (CVB) are associated with viral-induced heart disease and are among the leading causes of aseptic meningitis worldwide. Here we show that CVB entry into polarized brain microvasculature and aortic endothelial cells triggers a depletion of intracellular calcium stores initiated through viral attachment to the apical attachment factor decay-accelerating factor. Calcium release was dependent upon a signaling cascade that required the activity of the Src family of tyrosine kinases, phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 55 publications
2
62
3
Order By: Relevance
“…A wide range of cellular receptors has been observed in human EVs (reviewed by Merilahti et al, 2012). Although we did not examine the binding processes of EVs to the hCMEC/D3 cell surface, there is a large body of earlier experimental evidence to suggest that the intertypic variations in hCMEC/D3 susceptibility to EVs can be attributed to their propensity for using a wide range of receptors and internalization processes (Coyne et al, 2007;Bozym et al, 2010;Ylipaasto et al, 2010). For example, E-1 stands apart within the susceptibility spectrum of hCMEC/D3 cells to EV infection -a pattern that may be related to the fact that it is the only type known to bind integrin a 2 b 1 (Bergelson et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of cellular receptors has been observed in human EVs (reviewed by Merilahti et al, 2012). Although we did not examine the binding processes of EVs to the hCMEC/D3 cell surface, there is a large body of earlier experimental evidence to suggest that the intertypic variations in hCMEC/D3 susceptibility to EVs can be attributed to their propensity for using a wide range of receptors and internalization processes (Coyne et al, 2007;Bozym et al, 2010;Ylipaasto et al, 2010). For example, E-1 stands apart within the susceptibility spectrum of hCMEC/D3 cells to EV infection -a pattern that may be related to the fact that it is the only type known to bind integrin a 2 b 1 (Bergelson et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest a role of infected leukocytes in EV dissemination to the CNS through a 'Trojan horse' process. In vitro studies showed the susceptibility to different EVs of human vascular endothelial cells of different tissue origins (Conaldi et al, 1997;Saijets et al, 2003;Zanone et al, 2003;Liang et al, 2004;Bozym et al, 2010;Ylipaasto et al, 2010). In addition, PV-1 and CV-B3 induced different cell signalling and endocytosis pathways in human brain microvascular endothelial cells, which was suggestive of possible variations in BBB crossing between EV types (Coyne et al, 2007;Bozym et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…In these cells, CVB enters by a lipid raft-dependent, dynamin-independent mechanism that combines features of caveolar endocytosis and macropinocytosis (6,11). In contrast, CVB entry into polarized endothelial cells requires caveolar endocytosis, dynamin II, and unidentified Src family tyrosine kinases (SFKs) (13). In nonpolarized HeLa cells, dynamin II and lipid rafts are necessary for CVB entry, while clathrin and caveolin-1 are not (14).…”
mentioning
confidence: 99%
“…These nonreceptor tyrosine kinases readily autophosphorylate in bacteria and in vitro (131,132), suggesting that such substrates could be prepared in high yield for Abl-, Fyn-, and Lck-focused phosphatase assays. CVB3 infection also mobilizes Ca 2ϩ stores (133), and the Ca 2ϩ -activated phosphatase calcineurin disinhibits NFAT, a transcription factor whose activation in T cells promotes myocarditis (134). A calcineurinfocused NFAT phosphatase assay would enable a further elaboration of the host-cell signaling networks perturbed by CVB3.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of subcellular phosphatases is then quantified by phospho-ELISA using a panel of recognized full-length phosphoproteins. Building upon our past success with phosphorylated MAPKs (29), we add three new phosphosubstrates-phospho-MK2 (Thr 334 ), phospho-CREB (Ser 133 ), and phospho-STAT1 (Tyr 701 )-each with distinct patterns of localization and targeting by protein phosphatase enzymes (Fig. 1).…”
mentioning
confidence: 99%